Scaffolding Learning and its Application to Energy Conservation Field Training: A Bibliometric Analysis - Rohmatulloh, Rohmatulloh; Murtafiah, Nurul Hidayati; Dyah, Aspita; Zuhri, M. Tajudin; Sahlani, Lalan; Ibrohim, Iim (JURNAL APARATUR, 2023)
Scaffolding learning in training provides effective and efficient support to learners gradually according to their dynamic assessment achievements. Our contribution is to explore the trend of scaffolding learning in training research that has not been done in previous studies. Bibliometric analysis using Scopus scientific database for two decades (2004-2023). Data analysis used performance analysis, co-word analysis, and network visualization analysis. The results of research theme mapping show that instructional scaffolding has yet to be widely explored. Instructional scaffolding is a topic that provides a challenge for facilitators as a training solution in the field of energy conservation using a combination of learning forms, i.e., one-to-one, peer, and computer-based scaffolding.